Thymic Engraftment by in vitro-Derived Progenitor T Cells in Young and Aged Mice - Singh, Jastaranpreet; Mohtashami, Mahmood; Anderson, Graham; Zúñiga-Pflücker, Juan Carlos (Frontiers in Immunology, 2020)
T cells play a critical role in mediating antigen-specific and long-term immunity against viral and bacterial pathogens, and their development relies on the highly specialized thymic microenvironment. T cell immunodeficiency can be acquired in the form of inborn errors, or can result from perturbations to the thymus due to aging or irradiation/chemotherapy required for cancer treatment. Hematopoietic stem cell transplant (HSCT) from compatible donors is a cornerstone for the treatment of hematological malignancies and immunodeficiency. Although it can restore a functional immune system, profound impairments exist in recovery of the T cell compartment. T cells remain absent or low in number for many months after HSCT, depending on a variety of factors including the age of the recipient. While younger patients have a shorter refractory period, the prolonged T cell recovery observed in older patients can lead to a higher risk of opportunistic infections and increased predisposition to relapse. Thus, strategies for enhancing T cell recovery in aged individuals are needed to counter thymic damage induced by radiation and chemotherapy toxicities, in addition to naturally occurring age-related thymic involution. Preclinical results have shown that robust and rapid long-term thymic reconstitution can be achieved when progenitor T cells, generated in vitro from HSCs, are co-administered during HSCT. Progenitor T cells appear to rely on lymphostromal crosstalk via receptor activator of NF-B (RANK) and RANK-ligand (RANKL) interactions, creating chemokine-rich niches within the cortex and medulla that likely favor the recruitment of bone marrow-derived thymus seeding progenitors. Here, we employed preclinical mouse models to demonstrate that in vitro-generated progenitor T cells can effectively engraft involuted aged thymuses, which could potentially improve T cell recovery. The utility of progenitor T cells for aged recipients positions them as a promising cellular therapy for immune recovery and intrathymic repair following irradiation and chemotherapy, even in a post-involution thymus.